Modified single-carrier-based modulation technique for grid-connected three-level NPC converters - Watcharin Srirattanawichaikul (2018)
© 2016 IEEE. This paper presents a modified carrier-based modulation technique for the grid-connected three-level neutral-point-clamped (NPC) converter system. The proposed carrier-based modulation technique uses the single triangular carrier signal in generating the gate signals for three-level NPC converter. The control method of the grid-connected system is applied for the voltage oriented control scheme, which provides independent control active and reactive power flow into the utility grid and maintain the dc-link voltage constant. The feasibility of the developed proposed modulation technique for the grid-connected three-level NPC converter system is confirmed with experiment results, which is validated the performance and effectiveness of the presented method.